(3eONd GSJQGJjLj dOQGSGJ eJbOeI aj EOGQI GdJcdaI hJMdjd GdQHMjIs - (3KfGA Ydj(B, (3GdbHGfjs ((3GdGScfOQjI(B:s (3GdOGQ GdLGeYjI,s, 2006)
(3EOGQI GdJcGdja Ydi CSGS GdfTGW, GdJcGdja GdeYjGQjI hGdehGRfI GdeQfI hJMdjd GdGfMQGaGJ, GdehGRfI GdeQfI hJMdjd GfMQGaGJ GdJcGdja ZjQ GdeHGTQI, JMOjO JcdaI GdeNRhf, bQGQGJ GdJSYjQ hGOGQI GdJcdaI, JMdjd GdQHMjIs
Keywords: (3GdEOGQI(B- (3JcGdja s; (3GdeNRhfs